#TITLE_ALTERNATIVE# - GINANJAR (NIM : 223 09 009), YOUKE
One of the important stages in the seismic data processing is to identify and suppress the existence of multiple. Currently there are three methods of prediction and multiple subtraction that uses wave field concept, the method of wavefield extrapolation (WEMR), feedback (SRWEMR) and the inverse-scattering. WEMR method is quite successful method to eliminate multiple surfaces, but can not eliminate the multiple internal. In this study the method used is Surface-Related Wave Equation Multiple Rejection (SRWEMR). SRWEMR use feedback method in making predictions and multiple subtraction. SRWEMR method basically serves to eliminate multiple surfaces, but in this study used a SRWEMR method that has been developed (extended-SRWEMR) and used it to eliminate internal multiple. Internal multiple is the multiple produced by trapping of seismic waves between two reflectors. In this study used two types of seismic data, the synthetic seismic data and real seismic data. Synthetic data generated using the software Tesseral 2D. Real data is a 2D seismic data from Gorontalo Basin Line-9 which is a PPGL seismic survey around the north Sulawesi island. SRWEMR basic concept is that multiple events is the convolution of a primary event. By using the concept of wave field extrapolation, a primary event will convoluted with an operator that represents another primary event that will be obtained the multiple models. Later in the process of adaptive subtraction, seismic data shall be reduced by mutipel models that will be obtained multiple-free seismic data. By using the same concept, multiple internal would be predicted by convolution of a primary event, in which one of the primary event in the timereverse form. The results of the use of extended-SRWEMR method showed that this method is quite effective to suppress the existence of surface-related multiple and internal multiple from seismic marine data, especially for seismic marine data with limited offset, where multiple and primary reflector have small moveout differences.